Dimensionamiento de la malla de puesta a tierra para los laboratorios de alto voltaje de la universidad técnica de Cotopaxi. - Moya Piedra, Jinsop Rodrigo (2019)
The methodology for the dimensioning of the grounding grid is based on the IEEE STD 80/2000 norm of grounding meshes in Electrical Substations, which are of vital importance for the protection of the different equipment and measuring devices, transformation and control. The objective of the investigation is to determine the resistivity of the ground, as well as the pass and touch currents; at the same time guarantee the safety of people and equipment. To measure these indices and determine the percentage of affectation, a technical analysis was implemented; which consisted of conducting a study prior to the implementation of the grounding grid based on the data acquisition with the tellurometer. The result of the study affirmed that the land has a high resistivity value since it does not contain soluble salts, so it must be improved in order to obtain values that are within the IEEE STD 80-2000 standard. The resistivity is also influenced by moisture and minerals. This analysis is intended to provide the means to dissipate electrical currents to ground without exceeding the limits of operation of the network and equipment. For this we have made the calculations in three different designs (square, rectangular and "L" shaped mesh) proposed by the standard, in order to find the most optimal design for later implementation in the high voltage laboratory. The short circuit simulation was performed in the ETAP software in order to verify, if the mesh is well dimensioned so that no overvoltages occur and does not affect the grounding system.